Városjáró jogászképzés a debreceni jogi oktatás helyszíneinek alakulása, különös tekintettel a mai Kassai úti Campus történetére - Megyeri-Pálffi, Zoltán (Gerundium, 2018)
Moving Legal Education – The Evolution of Locality of the Legal Education in Debrecen with special regard to the History of Campus Kassai. The legal education in Debrecen has a long history. It started in the Reformed Collage of Debrecen in the middle of the 18th century. As a state university, it was established by the Act XXXVI of 1912. Until the main building of the University of Debrecen was completed (1932) the Faculty of Law had been operating in many places in the city. First, in the building of Reformed Collage, but some legal departments were in an apartment house on the main street. After 1932, the faculty of law had suitable offices in the main building of the University. Between 1949 and 1996 the legal education was suspended, and its offices were occupied by other departments. In the year of 1996 a solution had to be found, the restarted legal education needed new buildings. The new place was found on the field of ex-soviet barrack on the Kassai Street. This site was a cavalry barrack before the WWII. Some of the original buildings can still be found today, and many new buildings were built in the last couple of years e. g. library, student hostel, educational buildings. The faculty of law has also found its place on this campus. Its last moving was in the year of 2015, and it has a nice old-style group of buildings now.